2012
DOI: 10.4236/ojots.2012.24007
|View full text |Cite
|
Sign up to set email alerts
|

Gastroduodenal Artery Reconstruction as Salvage Procedure for Pancreas Head Ischemia during Transplantation: A Case Report

Abstract: Vascularization of the pancreatic allograft depends on the mesenteric and celiac arteries. During procurement inadvertent sectioning of the branches to the head of the pancreas can lead to ischemia and generally there is a need to remove the graft during the same transplant procedure. Knowledge of several unconventional revascularization techniques in the back table and other salvage procedures after reperfusion can be useful in deciding the fate of the graft once ischemia is established immediately after engr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Apart from PD, GDA is also important in other pancreatic surgeries . Bleeding from GDA, ASPDA or one of its branches can be very severe and difficult to control in pancreatic necrosectomy for walled off pancreatic necrosis involving the head and neck of pancreas.…”
Section: Pancreatic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from PD, GDA is also important in other pancreatic surgeries . Bleeding from GDA, ASPDA or one of its branches can be very severe and difficult to control in pancreatic necrosectomy for walled off pancreatic necrosis involving the head and neck of pancreas.…”
Section: Pancreatic Surgerymentioning
confidence: 99%
“…In this case, blood supply gets compromised as it remains fully dependent on DPA and splenic artery. If the blood flow from these vessels is not enough, GDA or RGEA have been reconstructed independently above the donor SMA to recipient's common iliac artery using an external iliac jump graft from donor GDA or RGEA to recipient's common iliac artery, thereby providing the blood supply to the transplanted organs .…”
Section: Pancreatic Surgerymentioning
confidence: 99%
“…Upon ligation, the duodenum and head of the pancreas become dependent upon the inferior pancreatoduodenal artery (IPDA) from the superior mesenteric artery, which becomes the main contributor of blood supply to the head of the pancreas and duodenum [9,10]. Therefore, some authors have suggested that hypoperfusion of the donor duodenum and head of the pancreas allograft may lead to perioperative complications of pancreas transplantation, including enteric or pancreatic leaks [8,[11][12][13]. However, this suggestion was not confirmed in a cohort-matched clinical trial.…”
Section: Introductionmentioning
confidence: 99%